Bioactive properties of the medicinal mushroom Leucopaxillus giganteus mycelium obtained in the presence of different nitrogen sources - Barros, Lillian (2007)
Leucopaxillus mushroom species are used in the chemical industry for extraction of clitocybin antibiotic and particularly the edible mushroom Leucopaxillus giganteus can be found in Northeast Portugal. Nevertheless, the production of its mycelium for pharmacological applications has not been explored. Herein, the mycelium obtained in the presence of four different nitrogen sources was investigated with regard to phenol production and antimicrobial and antioxidant properties. Phenol concentration increased along the growth time as a response to the oxidative stress and therefore free radical production. Although significant differences for mycelium growth between the nitrogen sources had not been observed, (NH4)2HPO4 proved to be the most appropriate to increase bioactive properties, leading to the highest phenol content and lowest EC50 and MIC values. The antimicrobial capacity was screened against Gram positive and Gram negative bacteria, and fungi. The samples selectively inhibited the growth of Gram positive bacteria, Staphylococcus aureus being the most susceptible one. Gram negative bacteria and fungi were resistant to the extracts. Antioxidant activity was calculated by the reducing power assay, the scavenging effect on DPPH radicals, and hemolysis and lipid peroxidation inhibition. Significantly negative linear regressions were established between phenols/flavonoids contents, which increased along the mycelia growth time and antioxidant activity.